Knowledge and attitude of medical students towards bioethics- A cross sectional study from a medical college in northern Tamil Nadu - Manoharan, Aravind; Iyengar, Madhusudan M; Nirupama, A Y; Kankanal , Nithya (Indian Journal of Community Health, 2021)
Studies have shown that a significant proportion of healthcare professionals were unaware of the universally recognized bioethical principles. The study was conducted to assess the knowledge and attitude towards bioethics among undergraduate medical students of a Medical College and also to find out the association of knowledge and attitude towards bioethics with other factors. This was a Cross Sectional study conducted at a medical college of Chengalpattu district between April to September of 2019. Study participants included medical undergraduate students from second academic year to fourth academic year of the medical college who had clinical exposure. Data was collected from a total of 224 subjects using a pretested, self-administered questionnaire. 89.3% of the respondents had poor knowledge about medical ethics. The prevalence of good+excellent knowledge about bioethics was highest among 17-19 years age group (95.8%) and least among >22 (60%) years age group, highest among those with <12 months of clinical exposure (100%) and least among those with 25-36 months of exposure (57.8%) and both these associations were found to be statistically significant by Chi square test. (P= 0.048 and <0.001 respectively). Majority of the subjects (>58%) had a favourable attitude towards the correct ethical practices with respect to most of the issues (11/15). However, majority of them (>53.1%) also had a favorable attitude towards certain issues (4/15) which are debatable. The most preferred sources for learning about medical ethics were seminars (81.7%), clinical discussions (78.1%) and lectures (57.1%). Majority of the subjects had poor knowledge about bioethics. The knowledge was better among students of earlier years of course compared to those in the later part. Majority of the subjects had a favorable attitude towards the correct ethical practices in most of the cases. The most preferred sources for learning about medical ethics were seminars, clinical discussions and lectures